Pharmacists’ response to anaphylaxis in the community (PRAC): a randomised, simulated patient study of pharmacist practice - Salter, Sandra M (BMJ Publishing Group, 2014)
OBJECTIVE: To evaluate how community pharmacists manage patients with anaphylaxis. DESIGN: A randomised, cross-sectional, simulated patient study of community pharmacist practice. SETTING: 300 metropolitan pharmacies located in Perth Australia, randomised to three groups of 100 pharmacies. Each group corresponded to a different epinephrine autoinjector: original EpiPen, new-look EpiPen or Anapen. PARTICIPANTS: 300 pharmacies were visited with 271 simulated patient visits included in the final analysis (88=original EpiPen, 92=new-look EpiPen, 91=Anapen). OUTCOME MEASURES: Primary anaphylaxis preparedness (readiness to treat acute anaphylaxis). Secondary anaphylaxis engagement (willingness to engage the patient in a discussion about their anaphylaxis). METHODS: Simulated patients approached pharmacists, using a standardised scenario, for assistance with epinephrine autoinjector use and advice about the use of antihistamines in anaphylaxis. Scores for each outcome were obtained based on the number of predefined statements addressed by the pharmacist during the consultation (maximum score=5 for preparedness and 8 for engagement). RESULTS: The mean anaphylaxis preparedness score was 2.39 points (SD 1.17). Scores for new-look EpiPen were significantly higher than for original EpiPen and Anapen (2.75 vs 2.38 points, p=0.027; 2.75 vs 2.03 points, p<0.001, respectively). Overall, 17.3% of pharmacists correctly demonstrated the epinephrine autoinjector. The mean anaphylaxis engagement score was 3.11 points (SD 1.73). Scores for new-look EpiPen were similar to original EpiPen and Anapen (3.11 vs 3.32 points; 3.11 vs 2.90 points, both p=0.42). Engagement was associated with preparedness. For each additional engagement point, preparedness increased by 7% (0.357 points; 95% CI 0.291 to 0.424; p<0.001). CONCLUSIONS: Pharmacists demonstrated reasonable knowledge of anaphylaxis symptoms and emergency care, but had poor epinephrine autoinjector technique and rarely discussed anaphylaxis action plans. Pharmacists who had a more comprehensive discussion about anaphylaxis with patients, were more prepared for anaphylaxis emergencies. Future research should evaluate the nature and significance of errors in pharmacists’ autoinjector technique.